Effect of the sowing method and fertilization on the onset of winter rape in the Forest-Steppe of Ukraine - Korotkova, I.; Drobitko А. (Scientific Progress & Innovations, 2024)
Growing demand for winter rape, as a basis for the production of animal feed, edible oil and fuel, with the simultaneous limitation of arable land and climate variability, requires an increase in its production. For this, it is necessary to improve the elements of the agronomic practice of growing this crop in order to ensure successful preparation of plants for winter and exit from it. The study aim is to determine the influence of the sowing method and fertilization on the development of winter rapeseed plants before the onset of winter in the Forest Steppe of Ukraine. Field experiment was carried out in 2023 in the soil and climatic conditions of the Myrhorod district of the Poltava region. The high-yield mid-ripening hybrid Mercedes was selected as the study object, which was sown early (August 9) at the sowing rate of 600,000 seeds per hectare. The influence of row width and fertilization system (width 19 cm in combination with Elixir Zorka NP 16 : 20+30 % SO 3+0.05 % B; width 35 cm with Nanovit Terra NP 9:20:5) on plant development was study during the period of active autumn vegetation. It was established the early sowing period of the Mercedes hybrid was carried out taking into account the weather and climatic conditions, which ensured the biological needs of the culture in active temperatures (1264.2 °С) and precipitation (291 mm), thanks to which the active autumn vegetation of plants lasted 101 days. As a result, with the onset of negative temperatures, the plants went into winter in the phase of ВВСН 19 (actually 9–10 true leaves). The winter rapeseed crops density was equal to 30–33 pcs./m2 for a row width of 19 cm and 32–34 pcs./m2 for a row width of 35 cm under these conditions. Measurements of the root neck diameter of the plants revealed a size of 8 mm at a row spacing of 19 cm and 10 mm – at the row spacing of 35 cm, while the root length was the same – 22 cm. Therefore, in the combination of factors, we can conclude about the optimal development of the plant. Study of the plants state during wintering by the method of monolith selection showed that all the selected plants recovered their vegetation within 7 days of being at a temperature of +19 °C, and there were no dead plants.